Efficacy of Bergazym® P100 (endo‐1, 4‐β‐xylanase) as a feed additive for chickens for fattening and weaned piglets. (30th October 2018) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The product Bergazym ® P100 contains a xylanase which is produced by a non‐genetically modified strain of Trichoderma reesei . The additive is available in a coated granular form and it is intended to be used as a zootechnical additive (functional group: digestibility enhancers) for chickens for fattening, and weaned piglets at the dose of 1, 500 EPU/kg feed. The production strain and the additive were fully characterised in a previous assessment of the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel). In that assessment, the FEEDAP Panel concluded that the additive is safe for chickens for fattening, weaned piglets and pigs for fattening and that the use of this product as a feed additive raises no concerns for consumers of food products obtained from animals receiving it or for the environment. The FEEDAP Panel also concluded that the additive is not irritant to skin or eyes but should be considered as a potential skin and respiratory sensitiser. The Panel evaluated the efficacy of the additive and concluded that it has a potential to be efficacious in pigs for fattening at 1, 500 EPU/kg feed. However, the Panel could not conclude regarding the efficacy of the additive for chickens for fattening and weaned piglets due to insufficient data/information. The applicant has now provided supplementary information in order to complement the information available supporting the efficacy of the additive. With the newly submitted efficacy studies and clarifications, the Panel concluded that the additive has a potential to be efficacious in chickens for fattening and weaned piglets at 1, 500 EPU/kg feed.